ANALISIS PENDAPATAN DAN STRATEGI PENGEMBANGAN BUDIDAYA RUMPUT LAUT DI PULAU PAHAWANG KECAMATAN PUNDUH PIDADA KABUPATEN PESAWARAN - Dede Putri; Wuryaningsih Dwi Sayekti; Novi Rosanti (Lampung University, 2014)
This research aimed to analyze the income and strategies in the development of seaweed cultivation. This research was conducted in Pahawang Island, Punduh Pidada District, Pesawaran Regency. This research used cencus method involving all of 20 seaweed cultivators. The analysis method in this study were income determination and SWOT analysis. The results showed that the cultivation of seaweed in Pahawang Island was worth to develope. The average income of cash cost and total cost are Rp2,011,000 and Rp686,965 for each production process. Combination value IFE was 1.6 and value of EFE was 0.4 in the IE matrix shows that the position of the business in quadran I. This suggests that the cultivation of seaweed on Pahawang Island are at the area growth. The three priority strategies for developing the seaweed cultivation were improvement of the cultivator training skills; extensification of cultivation area; and increase the production of good quality seaweed to expand the marketing network. Keywords : income, seaweed, strategy development, SWOT analysis